MU‘ALLAQ HADITHS WITH ṢĪGHAH AL-TAMRĪḌ IN ṢAḤĪḤ AL-BUKHĀRĪ AND THEIR IMPLICATIONS FOR ISLAMIC JURISPRUDENCE - Hikmah, Halimatul; Alamuddin, Muhammad (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2024)
Several hadiths in Ṣaḥīḥ al-Bukhārī, whose Several hadiths in Sahih al-Bukhari, whose authenticity is agreed upon by the majority of scholars, are considered problematic because they are narrated using the mu‘allaq method. This study aims to uncover the reasons for the presence of mu‘allaq hadiths in Sahih al-Bukhari, focusing on hadiths narrated in passive form (ṣīgah al-tamrīḍ) and their implications for Islamic law. Data collection techniques involved literature review and descriptive qualitative data analysis. This study found that there are ten hadiths narrated with ṣīgah al-tamrīḍ in Sahih al-Bukhari. Five reasons were identified for why al-Bukhari used this method of narration: summarization, layyin (weakness) in the narrator, ‘illah (defect) in the narrator, the narrator's ḍa’īf (weakness), and disagreement on the narrator's authority. Of the ten hadiths found, only one hadith influenced differences in scholarly opinion, namely the hadith that explains the thigh as 'awrah. This finding is expected to provide a better understanding of al-Bukhari's use of ṣīgah al-tamrīḍ and its impact on the interpretation of Islamic law. [Beberapa hadis dalam Ṣaḥiḥ al-Bukhārī, yang kehujahannya disepakati mayoritas ulama, dianggap bermasalah karena diriwayatkan dengan metode mu‘allaq. Penelitian ini bertujuan untuk mengungkap alasan adanya hadis-hadis mu‘allaq dalam Ṣaḥīḥ al-Bukhārī, dengan fokus pada hadis yang diriwayatkan dalam bentuk pasif (ṣīgah al-tamrīḍ) dan implikasinya terhadap hukum Islam. Teknik pengumpulan data dilakukan melalui kajian kepustakaan dan analisis data kualitatif deskriptif. Penelitian ini menemukan bahwa dalam Ṣaḥīh al-Bukhārī, terdapat sepuluh hadis yang diriwayatkan dengan ṣīgah al-tamrīḍ. Ditemukan lima alasan mengapa al-Bukhārī menggunakan metode periwayatan ini: adanya peringkasan, layyin dalam rawi, ‘illah (kecacatan) dalam rawi, ḍa’īf-nya rawi, dan adanya perselisihan dalam ke-ḥujjah-an rawinya. Dari sepuluh hadis yang ditemukan, hanya satu hadis yang memengaruhi perbedaan pendapat ulama, yaitu hadis yang menjelaskan tentang paha sebagai aurat. Penemuan ini diharapkan dapat memberikan pemahaman yang lebih baik mengenai penggunaan ṣīgah al-tamrīd oleh al-Bukhārī dan dampaknya terhadap interpretasi hukum Islam.]